Lactic acid production using enteroccos faecalis in hydrolyzed sago starch by repeated batch fermentation - Afri Shafrulniiza, Binti Shafriil (Universiti Malaysia Sarawak, UNIMAS, 2012)
The production of lactic acid (LA) by utilizing the raw carbon source of hydrolyzed sago starch (HSS) using newly isolate Enterococcus faecalis strain by repeated batch fermentation (RBF) methodology was investigated in this study. The aim was to investigate if E. faecalis is able to produce LA at high concentration for a possible industrial application. The fermentation was carried out at pH 6.5 by addition of sodium hydroxide, controlled at 40°C and agitated at 250 rpm. HSS concentration was varied ranging from 30 to 100 g/l to as consequence of the increasing of biomass. The results showed that the production of LA is the highest during the fourth cycle providing high concentration of HSS, 100 g/l at the beginning of the cycle, despite low volumetric productivity and yield. However, it was found that the optimum HSS concentration for the LA production using this strain is at 80 g/l which produced volumetric productivity and yield of 1.27 g/lh and 0.54 g/g, respectively. In overall, the total LA production throughout the 7 cycles of RBF is 130.53 g/l with volumetric productivity and yield of 1.02 g/lh and 0.54 g/g, respectively.